The Economic Nature of the Organizational and Economic Mechanism for Corporate Social Responsibility of Business - BONDARUKТ.; BONDARUKІ. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The issue of theoretical foundations of the economic nature of the organizational and economic mechanism of social responsibility of business is elaborated on. It is demonstrated that the organizational and economic basis for the mechanism designed to regulate corporate social responsibility is consisted of government regulation, shared regulation and self-regulation of corporate social responsibility. The central objectives of the regulatory policy of corporate social responsibility are highlighted: to engage business entities in solving social and economic problems; to introduce the innovation-driven model for fostering the social responsibility; to create new jobs and reduce unemployment. The authors’ definition of the organization and economic mechanism for corporate social responsibility is proposed: a set of organizational and economic measures aimed to trigger interactions between business entities and the state for fostering social responsibility, implemented through regulatory acts and on the business entities’ initiative, in order to attain the sustainable development through creating partner relations of the state, business and society. It is demonstrated that the organizational and economic mechanism for corporate social responsibility constitutes a multi-tier hierarchical system of organizational and economic components (functional components: entities, objects, principles), tools for mechanism implementation (tools of organizational, economic and social nature), and methodological support (administrative, economic, index and rating methods).